The Performance of Balinese Gilt Reared Intensively and Supplemented With Probiotic - Budaarsa, K.; Puger, A. W.; Putri, T. I.; Udayana, I D.G.A. (Journal of Veterinary and Animal Sciences; Vol 1 No 1 (2017), 2017)
Study to improve the performance of Balinese gilt reared by intensive management including good quality rationssupplemented with yeast culture as a source of probiotics has been conducted. Randomized Block Design (RBD) were used in this study. Sixteen post weaning (two months old) gilts weight 10-12kg were divided into 4 groups: (i)ration control, R1 (ration containing 18% concentrate, 40% corn and 41% rice bran and 1% mineral); (ii) R2 (R1+ 0.20% probiotics; (iii) R3 (R1+ 0.25% probiotics and R4 (R1 + 0.30% probiotics) with 4 replications. Parameters measured including: feed intake, body weight gain, feed conversion ratio (FCR) and digestibility of the ration. Results showed that feed intake, daily weight gain and feed digestibility increased significantly (P <0.05) in the gilt receiving probiotic treatment, on the other hand the value of FCR decreased significantly compared to the control group. It is concluded that the addition of probiotics in rations significantly improve the performance of Balinese gilt.